An experimental investigation on the fatigue crack growth behaviour of AISI/SAE 1045 under load sequences containing underloads. Issue 4 (14th November 2018) - Richter, Hannes; Sander, Manuela
Abstract: The estimation of load interaction effects is essential for residual lifetime calculations of components with cracks. Whereas overloads are widely investigated, there is still no consensus about the effects and mechanisms of underloads. For this reason, load sequences containing underloads are experimentally examined within this paper. Because K max and R are not appropriate for describing the cyclic crack tip loading at tension/compression loading, the σ tip concept is used to quantify the crack driving force at compressive loads. Among others, the tests also include load sequences that have not been reported in the literature yet like underloads that are applied at a certain distance after an overload. The influence of underloads on crack arrest is also investigated. The experimental tests are performed with the tool steel AISI/SAE 1045.